THE NEUROPROTECTIVE EFFECT OF Rho-KINASE INHIBITION IN 1-METHYL-4-PHENYLPYRIDINIUM (MPP+)-INDUCED CELLULAR MODEL OF NEURODEGENERATION - Blagojević, Sanja; Jeremić, Marija; Jovanović-Tucović, Maja (Medicinski podmladak, 2022)
Introduction: The 1-methyl 4-phenyl 1,2,3,6-tetrahydropiridium (MPTP) induced model of neurodegeneration in Parkinson’s disease (PD) is one of the most commonly used experimental models. MPTP, or rather its metabolite MPP+, leads to inhibition of mitochondrial complex I, an increase in free radicals’ production and ATP depletion, all resulting in cellular demise and death. Rho-kinase is an enzyme involved with numerous cell regulatory mechanisms, such as cytoskeleton organization, axonogenesis, vesicular transport regulation and apoptosis regulation, which are important for cell survival. Aim: Our aim was to investigate the effects of Rho-kinase inhibition on the MPP+ induced model of neurodegeneration and the role of Akt and adenosine monophosphate-activated protein kinase (AMPK) signaling pathways in this process. Materials and methods: The experiments were performed on the human neuroblastoma SH-SY5Y cell line. The MTT test was used to measure the viability of the cells after the MPP+ and/or Rho-kinase inhibitor, fasudil, treatments. Changes in activation levels, or rather expression of pAMPK, pAkt, AMPK and Akt, were measured with the immunoblotting method, and the protein levels were quantified by densitometry. Results: MPP+ treatment caused a dose-depedent decrease in cellular viability, compared to the control group (untreated cells), while fasudil treatment prior to MPP+ exposure, improved cell viability a dose-dependent increase, compared to MPP+ treatment. Analysis of activation status of target proteins showed an increase in Akt activation after the fasudil treatment, while the AMPK activation was not significantly changed. Conclusion: Inhibition of Rho-kinase using fasudil causes a decrease in MPP+ induced cell death, which is possibly mediated by an activation of the Akt/PI3K signaling pathway.